Modernity and the text : revisions of German modernism - Huyssen, Andreas; Bathrick, David (Columbia University Press, 1989)
The study of Austrian and German modernist literature has a long and venerable history in this country. There have been no attempts yet, however, to reassess German and Austrian literary modernism in light of current discussion of modernity and postmodernity. Addressing a set of historical and theoretical questions central to current reevaluations of modernism, this volume presents American readers with a state-of-the-art account of German modernism studies in the eighties. Essays by Jochen Schulte-Sasse, Russell A. Berman, Peter Uwe Hohendahl, Judith Ryan, Mark Anderson, Klaus R.